Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1108/ijcst-04-2020-0052
|View full text |Cite
|
Sign up to set email alerts
|

Development of gait assistive clothing-typed soft wearable robot for elderly adults

Abstract: PurposeThe purpose of this research was to develop clothing-typed soft wearable robot embedded with textile-based actuators on ankles for elderly adults needing gait assistance.Design/methodology/approachDesign guidelines were developed and they included function (type, targeting area, routing line and anchor points), design (size/fit, fabric/material, fastener, detail, color) and actuator (shape memory alloy type, size, deformation type, integration material, integration technique and evaluation method). Fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 43 publications
(66 reference statements)
1
9
1
Order By: Relevance
“…55 The higher the frequency of each working motion and the physical burden on the occupation, the more the incidence of musculoskeletal diseases is expected to increase. 22 Men (M = 4.94, SD = 0.23) considered wearability to be more important than women did (M = 4.75, SD = 0.61) ( t = 1.496, p = .001), and men had more intentions to use/wear clothing-type wearable robots for strength support ( t = 1.562, p < .01). Eom 22 found that people avoid wearing conventional work clothes because they are uncomfortable, which can decrease work efficiency.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…55 The higher the frequency of each working motion and the physical burden on the occupation, the more the incidence of musculoskeletal diseases is expected to increase. 22 Men (M = 4.94, SD = 0.23) considered wearability to be more important than women did (M = 4.75, SD = 0.61) ( t = 1.496, p = .001), and men had more intentions to use/wear clothing-type wearable robots for strength support ( t = 1.562, p < .01). Eom 22 found that people avoid wearing conventional work clothes because they are uncomfortable, which can decrease work efficiency.…”
Section: Resultsmentioning
confidence: 96%
“…22 Men (M = 4.94, SD = 0.23) considered wearability to be more important than women did (M = 4.75, SD = 0.61) ( t = 1.496, p = .001), and men had more intentions to use/wear clothing-type wearable robots for strength support ( t = 1.562, p < .01). Eom 22 found that people avoid wearing conventional work clothes because they are uncomfortable, which can decrease work efficiency. Therefore, modifications should be made, such as reducing the burden by wearing lightweight work clothes.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations